Effect of Wirefeed Rate On The Morphology Of A Surface Machined Using WEDM - Mouralova, Katerina; Kovar, Jiri; Benes, Libor; Osicka, Karel (Manufacturing Technology Journal, 2016)
Wire electrical discharge machining (WEDM) is an unconventional technology of machining that uses physical phenomena for material cutting. During wire electrical discharge machining craters are formed on the workpiece surface, and blended and molten material of both workpiece and wire electrode get stuck here due to diffusion processes. The study deals with the assessment of the influence of wire feed rate on quantitative and qualitative evaluations of craters on the workpiece made of X155CrVMo12-1 alloy tool steel. The diffusion phenomena that had occurred on the surface during the process of cutting were studied using light microscopy. Attention was also given to the detail study of the used brass electrode where the level of wear and degradation in terms of the quality of morphology were studied after the process of cutting.
Keywords: WEDM; Electrical Discharge Machining; steel X155CrVMo12-1; surface layer; wire feed